2020
DOI: 10.1108/ijqrm-03-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

Product recall strategy in the supply chain: utility and culture

Abstract: PurposeProduct recalls have the potential to damage firm and consumer quality reputation. While globalization has brought about various economic benefits, expanding supply chain networks have also made it more difficult for downstream organizations to manage product recall strategy. This study aims to examine the role of culture on a manufacturer's initiation of a recall and the severity of the remedy chosen for the product recall.Design/methodology/approachUtilizing the culture-specific argument, this study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…associated with Industry 4.0 (Fiorentino et al , 2020; Nižetić et al , 2019; Perri et al , 2020) are shifting the way traditional warehouses were operated. Smart technologies have generated tremendous opportunities for improving warehouses' safety and service over the past decade and causing rapid digitalization of organizations in the sustainable SC domain (Schniederjans and Khalajhedayati, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…associated with Industry 4.0 (Fiorentino et al , 2020; Nižetić et al , 2019; Perri et al , 2020) are shifting the way traditional warehouses were operated. Smart technologies have generated tremendous opportunities for improving warehouses' safety and service over the past decade and causing rapid digitalization of organizations in the sustainable SC domain (Schniederjans and Khalajhedayati, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Apple, Micron, Intel, Samsung, and TSMC recently made friendshoring moves (Tran, 2022). Furthermore, Massini et al (2010) and Schniederjans and Khalajhedayati (2021) found that MNFs with an implementable corporate strategy tended to consider a broader set of offshoring drivers such as risks, service quality, cultural compatibility, and geographical proximity rather than taking into account costs alone when selecting the most desirable offshoring location. That is to say, the MNF's mere focus on costs for offshoring decisions was evidence of an ill-informed corporate strategy (Remko, 2020).…”
mentioning
confidence: 99%